2016
DOI: 10.1371/journal.pone.0146156
|View full text |Cite
|
Sign up to set email alerts
|

Single Agent Antihypertensive Therapy and Orthostatic Blood Pressure Behaviour in Older Adults Using Beat-to-Beat Measurements: The Irish Longitudinal Study on Ageing

Abstract: BackgroundImpaired blood pressure (BP) stabilisation after standing, defined using beat-to-beat measurements, has been shown to predict important health outcomes. We aimed to define the relationship between individual classes of antihypertensive agent and BP stabilisation among hypertensive older adults.MethodsCross-sectional analysis from The Irish Longitudinal Study on Ageing, a cohort study of Irish adults aged 50 years and over. Beat-to-beat BP was recorded in participants undergoing an active stand test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 31 publications
3
39
1
5
Order By: Relevance
“…A large study by Irish authors looked into the effects of monotherapy for hypertension (ACE inhibitors, betablockers, calcium blockers and diuretics) on the prevalence of orthostatic hypotension in older patients with hypertension. The research showed that only monotherapy with beta-blockers was coupled with long-term and persistent orthostatic hypotension (16). A group of French authors demonstrated a higher occurrence of orthostatic hypotension with the use of diuretics and calcium blockers, while ACE inhibitors were not connected to a significant postural drop in blood pressure (17).…”
Section: Discussionmentioning
confidence: 99%
“…A large study by Irish authors looked into the effects of monotherapy for hypertension (ACE inhibitors, betablockers, calcium blockers and diuretics) on the prevalence of orthostatic hypotension in older patients with hypertension. The research showed that only monotherapy with beta-blockers was coupled with long-term and persistent orthostatic hypotension (16). A group of French authors demonstrated a higher occurrence of orthostatic hypotension with the use of diuretics and calcium blockers, while ACE inhibitors were not connected to a significant postural drop in blood pressure (17).…”
Section: Discussionmentioning
confidence: 99%
“…For example, other authors showed that nitrates and diuretics15 and β-blockers16 are particularly related to orthostatic hypotension and syncope in older patients. Large trials with a longer follow-up are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Частота ОГ неодинакова на фоне лечения антигипертензивными препаратами разных классов. Так, она реже возникает на фоне терапии ингибиторами АПФ, блокаторами рецепторов ангиотензина II и блокаторами кальциевых каналов по сравнению с b-адреноблокаторами и тиазидными диуретиками [54][55][56][57]. В исследование PARTAGE показано, что b-адреноблокаторы в большей степени увеличивают риск развития ОГ из-за повышенной симпатомиметической активности, тогда как среди пациентов, принимающих блокаторы рецепторов ангиотензина II, ОГ встречается реже [54].…”
Section: лекарственные средства предрасполагающие к развитию огunclassified
“…В исследование PARTAGE показано, что b-адреноблокаторы в большей степени увеличивают риск развития ОГ из-за повышенной симпатомиметической активности, тогда как среди пациентов, принимающих блокаторы рецепторов ангиотензина II, ОГ встречается реже [54]. В исследовании TILDA [56], которое включало 4467 пациентов с ОГ, применение α-адреноблокаторов и b-адреноблокаторов, но не блокаторов кальциевых каналов, было статистически значимо взаимосвязано с наличием ОГ и усугубляло симптомы ортостаза. Кроме того, наличие этих симптомов было независимым предиктором возникновения в дальнейшем обмороков.…”
Section: лекарственные средства предрасполагающие к развитию огunclassified